2022
DOI: 10.1002/ijc.34383
|View full text |Cite
|
Sign up to set email alerts
|

Association between a polymorphic variant in the CDKN2B‐AS1/ANRIL gene and pancreatic cancer risk

Abstract: Genes carrying high‐penetrance germline mutations may also be associated with cancer susceptibility through common low‐penetrance genetic variants. To increase the knowledge on genetic pancreatic ductal adenocarcinoma (PDAC) aetiology, the common genetic variability of PDAC familial genes was analysed in our study. We conducted a multiphase study analysing 7745 single nucleotide polymorphisms (SNPs) from 29 genes reported to harbour a high‐penetrance PDAC‐associated mutation in at least one published study. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…(supplementary file2). A few examples are as follows: a) CDKN2B-AS1 and ‘Pancreatic Ductal Carcinoma,’ a study by Giaccherini et al reported that rs1412832 polymorphism, that is situated in the CDKN2B-AS1/ANRIL, showed a genome-wide significant association with increased risk of developing pancreatic ductal adenocarcinoma [36]. b) ATXN8OS and ‘drug response’, Luo et al conducted a study using glioma xenograft models to show that ATXN8OS inhibited temozolomide (TMZ)-resistance of glioma [37].…”
Section: Discussionmentioning
confidence: 99%
“…(supplementary file2). A few examples are as follows: a) CDKN2B-AS1 and ‘Pancreatic Ductal Carcinoma,’ a study by Giaccherini et al reported that rs1412832 polymorphism, that is situated in the CDKN2B-AS1/ANRIL, showed a genome-wide significant association with increased risk of developing pancreatic ductal adenocarcinoma [36]. b) ATXN8OS and ‘drug response’, Luo et al conducted a study using glioma xenograft models to show that ATXN8OS inhibited temozolomide (TMZ)-resistance of glioma [37].…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, rs1412832 polymorphism demonstrated a genome-wide significant association with increased risk of pancreatic cancer. 32 CDKN2B-AS1 rs1011970 was reported as a risk variant for melanoma and correlated with reduced expression of CDKN2B-AS1, 33 whereas rs11515 polymorphism was connected to breast cancer and elevated expression of CDKN2B-AS1. 34 In addition, associations of rs4977756 and rs1412829 with glioma reached a genome-wide threshold.…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2B‐AS1 rs2151280 has been shown to affect susceptibility to basal cell carcinoma 30 and progression‐free survival in multiple myeloma 31 . Moreover, rs1412832 polymorphism demonstrated a genome‐wide significant association with increased risk of pancreatic cancer 32 . CDKN2B‐AS1 rs1011970 was reported as a risk variant for melanoma and correlated with reduced expression of CDKN2B‐AS1 , 33 whereas rs11515 polymorphism was connected to breast cancer and elevated expression of CDKN2B‐AS1 34 .…”
Section: Introductionmentioning
confidence: 99%
“…PDAC is a complex disease with a multifactorial etiology for which several epidemiologic risk factors have been identified, including age, type 2 diabetes mellitus, smoking, alcohol consumption and chronic pancreatitis and the presence of non-invasive cyst, such as intraductal papillary mucinous neoplasm (IPMN) [3][4][5][6][7][8][9] . Moreover, genetic factors play an important role in the development of PDAC, as highlighted by the results reported by several genome-wide association studies (GWAS) and more focused reports on specific genomic regions [10][11][12][13][14][15][16][17][18][19][20][21][22][23] . PDAC typically affects people in their late adult life, is most frequently diagnosed among people aged 65-74 with a median age of onset of 70 years (accessed on August 25, 2022, https://seer.cancer.gov/statfacts/html/pancreas.html ).…”
Section: Introductionmentioning
confidence: 99%